2020
DOI: 10.1101/2020.05.14.093583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Viral RNA Fragments in Human iPSC-Cardiomyocytes following Treatment with Extracellular Vesicles from SARS-CoV-2 Coding-Sequence-Overexpressing Lung Epithelial Cells

Abstract: ABSTRACTThe novel coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved into a worldwide pandemic. Early data suggest that the prevalence and severity of COVID-19 appear to be higher among patients with underlying cardiovascular risk factors. Despite the expression of angiotensin-converting enzyme 2 (ACE2), a functional receptor for SARS-CoV-2 infection, in cardiomyocytes, there has been no conclusive evidence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 12 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…The in vitro cell culture and tissue models will also be helpful in studying SARS-CoV-2 infection, cytotoxicity, molecular mechanisms, and drug or therapy effects on cells. As multiple studies have shown, the iPSC-derived cardiomyocytes could be transfected by SARS-CoV-2 and develop cytotoxic effects and death [ 61 , 136 , 137 , 138 , 139 , 140 ]. The use of cardiac organoids will be instructive to mimic COVID-19 infection of the heart but, as of now, there is no study available.…”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%
“…The in vitro cell culture and tissue models will also be helpful in studying SARS-CoV-2 infection, cytotoxicity, molecular mechanisms, and drug or therapy effects on cells. As multiple studies have shown, the iPSC-derived cardiomyocytes could be transfected by SARS-CoV-2 and develop cytotoxic effects and death [ 61 , 136 , 137 , 138 , 139 , 140 ]. The use of cardiac organoids will be instructive to mimic COVID-19 infection of the heart but, as of now, there is no study available.…”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%
“…Moreover, exosomes secreted by the adult CPe can be hijacked to serve as a vehicle for the spread of virus infection from periphery to the CNS as shown for human polyomavirus (JCPyV) [131]. Intriguingly, CP-mediated release of exosomes may underlie transmission of SARS-coronavirus 2 (SARS-CoV-2) within the CNS as the CP displays relatively-high expression levels of ACE2 receptor, which is engaged by SARS-CoV-2 for active invasion of host cells [132][133][134][135].…”
Section: Exosomes In Cp-csf Signallingmentioning
confidence: 99%
“…Interestingly, cardiac injury has been reported in COVID-19 patients [ 100 ], even in the absence of coronary arteries obstruction [ 101 ], therefore unlikely to be caused by altered coagulation observed in these patients [ 102 ]. Furthermore, a mechanism of entry of SARS-CoV-2 in cardiomyocytes has been recently proposed [ 103 ]. In light of these evidences, should the cardiac injury, observed in COVID-19 patients, be proven to be due, at least in part, to cavinin-1 sequestration by viral N, then inhibitors of the N-cavinin1 interaction may be valuable drug candidates.…”
Section: Discussionmentioning
confidence: 99%